THE IMPACT OF CULINARY TOURISM ON THE ECONOMY OF COASTAL COMMUNITIES IN TIRAM BEACH NAGARI TAPAKIS SUB DISTRICT ULAKAN TAPAKIS PADANG PARIAMAN REGENCY WEST SUMATERA PROVINCE - Dela Sintya; Trisla Warningsih; Hamdi Hamid (Fakultas Perikanan dan Kelautan, Universitas Riau, 2019)
This study aimed to utilize the fish bone waste from different types of fish, Pangasius sp., Clarias sp., Paraplotosus sp. as a high calcium of bone flour and determine the quality characteristics of fish bone flour which was produced. The method used was a non-factorial Completely Randomized Design (CRD), with different types of fish bones as treatments which consisting of 3 levels: Pangasius sp. bone (Tp), Clarias sp. bone (Tl), and Paraplotosus sp. bone (Ts) with 3 replications and 9 units of experimental units. The parameters tested were organoleptic, proximate analysis, calcium, phosphorus and whiteness degrees. The results showed that the Pangasius sp. bone flour (Tp) was the best treatment with characteristics of brilliant appearance, the distinctive aroma of fish was still felt, smooth and dry texture, as well as whiteness degrees that the best treatment in walking catfish bone flour with value 81.30%, referred to whiteness degrees of flour, it is below the range of 80-90%. Meanwhile the best proximate value was obtained in Paraplotosus sp. bone treatment (Ts) with moisture, ash, fat, protein, carbohydrate, calcium and phosphorus content was 5.71%, 54.60%, 2.57%, 25.21%, 10.83%, 38.4%, and 33.9%.